Pengaruh Persepsi Keamanan dan Kepercayaan Terhadap Loyalitas Nasabah: Studi Kasus Serangan Siber di Bank Syariah Indonesia - Zamzami Akromi Lubis; Fauzi Arif Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the effect of perceived security and trust on customer loyalty at Bank Syariah Indonesia in Medaan City, this research was conducted at Islamic Bank customers. The type of research used is quantitative research. Sampling using saturated sampling technique, because researchers only took a sample of employee respondents totaling 97 respondents. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression, classical assumption test, F hypothesis test, t hypothesis test, coefficient of determination. The results of the research conducted show that the coefficient of determination (adjusted R square) is 0.604 or 60.4%. That perceived security and trust simultaneously affect customer loyalty at Bank Syariah Indonesia. Perceived Security affects Customer Loyalty at Bank Syariah Indonesia. Meanwhile, trust partially affects customer loyalty at Bank Syariah Indonesia.